ANALYSIS OF BRAND IMAGE, BRAND TRUST, CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION THROUGH PERCEIVED VALUE BANK SYARIAH INDONESIA (STUDY AT BSI KCP KRAKATAU) - Ahmad Fadli; Beby Karina F. Sembiring; Syafrizal Helmi Situmorang (CV. Radja Publika, 2023)
This study examines how Brand Image, Brand Trust, and Customer Experience affect Customer Satisfaction through Bank Syariah Indonesia Krakatau branch Perceived Value. Quantitative associative research. This study uses primary and secondary data. Descriptive statistics, path, and path diagram analyses are used. This study includes Bank Syariah Indonesia Krakatau clients who use multiple products. This study has 353 respondents. This study found that Brand Image has a positive and significant effect on Customer Satisfaction and Perceived Value, Brand Trust has a negative and insignificant effect, and Customer Experience has a positive and significant effect on both.